Housekeeping gene stability in Pesudomonas aeruginosa PAO1 under the pressure of commonly used antibiotics in molecular microbiology assays - Meng, Lingning; Cao, Xiaoli; Li, Chuchu; Li, Jia; Xie, Hui; Shi, Jiping; Han, Mei; Shen, Han; Liu, Chang (Frontiers in Microbiology, 2023)
Pseudomonas aeruginosa is an opportunistic human pathogen notorious for its remarkable capacity of multi-drug resistance, and has become one of the most important model bacteria in clinical bacteriology research. Quantitative real-time PCR is a reliable method widely used in gene expression analysis, for which the selection of a set of appropriate housekeeping genes is a key prerequisite for the accuracy of the results. However, it is easy to overlook that the expression level of housekeeping gene may vary in different conditions, especially in the condition of molecular microbiology assays, where tested strains are generally cultured under the pre-set antibiotic selection pressures, and how this affects the stability of commonly used housekeeping genes remains unclear.In this study, the expression stability of ten classic housekeeping genes (algD, gyrA, anr, nadB, recA, fabD, proC, ampC, rpoS, and rpsL) under the pressure of eight laboratory commonly used antibiotics (kanamycin, gentamycin, tetracycline, chloramphenicol, hygromycin B, apramycin, tellurite, and zeocin) were tested. Results showed that the stability of housekeeping gene expression was indeed affected by the types of antibiotics added, and of course the best reference gene set varied for different antibiotics.This study provides a comprehensive summary of the effects of laboratory antibiotics on the stability of housekeeping genes in P. aeruginosa, highlighting the necessity to select housekeeping genes according to the type of antibiotics used in the initial stage of experiment.